2012
DOI: 10.1007/s10530-012-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Water brownification may increase the invasibility of a submerged non-native macrophyte

Abstract: Environmental conditions and human activities play a significant role in structuring novel assemblages of native and non-native species. Ongoing and future climatic change may alter the performance of native and non-native species and their biotic interactions. In the northern hemisphere, expected climate changes include warmer temperatures and higher precipitation, the latter of which may increase dissolved organic carbon (humic) concentrations, resulting in browner water in aquatic ecosystems (brownification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…Mormul et al (2012) observed that although temperature did not seem to have an effect, water ''brownification'' (increased organic carbon concentrations, resulting in browner water) owing to changing climatic conditions resulted in increased growth of invasive E. canadensis and decreased growth of native species. They suggest that this brownification gives E. canadensis a competitive advantage, facilitating increasing future spread.…”
Section: Competitionmentioning
confidence: 98%
“…Mormul et al (2012) observed that although temperature did not seem to have an effect, water ''brownification'' (increased organic carbon concentrations, resulting in browner water) owing to changing climatic conditions resulted in increased growth of invasive E. canadensis and decreased growth of native species. They suggest that this brownification gives E. canadensis a competitive advantage, facilitating increasing future spread.…”
Section: Competitionmentioning
confidence: 98%
“…Furthermore, they can indirectly affect vegetation composition by releasing nutrients and organic compounds through excretion following the consumption of large amounts of macrophytes (Newman, 1991;Vanni, 2002). The microbial degradation of dissolved organic compounds into humic acids can then cause brownification of the water (Roulet & Moore, 2006;Graneli, 2012), which affects light availability and vegetation composition (Mormul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mesocosm Experiments as a Tool for Ecological Climate-Change Research consequences of climate change, such as increases in run-off Vinebrooke, 2009), salinisation (Herbst andBlinn, 1998;Jeppesen et al, 2007), and browning by increasing concentrations of humic substances in the water column (Mormul et al, 2012;. Some of the ultimate consequences of climate change, such as cycling of nitrogen (Veraart et al, 2011) and carbon (Atwood et al, 2013;Flanagan and McCauley, 2010;Moss, 2010;Yvon-Durocher et al, 2010a,b, 2011a, benthic-pelagic or terrestrial-aquatic coupling (Boros et al, 2011;, or the implications of biodiversity change for ecosystem stability (Thompson and Shurin, 2011) have only recently been addressed using pond mesocosms.…”
mentioning
confidence: 99%